An introduction to body vandalism: What is it? Who does it? When does it happen?. (January 2017) - Krieger, Heather; DiBello, Angelo M.; Neighbors, Clayton
Abstract: A number of typical consequences for alcohol and other substances have been well documented. However, a specific category of consequences which has received no attention in the existing literature includes acts (other than sexual assault) committed upon incapacitated individuals. We have termed this behavior body vandalism (BV), defined as the direct manipulation of an incapacitated individual through the addition of markings, objects or substances, removal of property or hair, or relocation of a body. The purpose of this paper is to provide a preliminary examination of rates of experiencing and variations in positive and negative perceptions of this behavior from the victim's perspective. A pilot study was conducted aimed at examining the rates and demographic characteristics of body vandalism in a national sample of 981 adults. The majority of individuals had witnessed BV, half had perpetrated, and over 40% had been a victim in their lifetime. Rates of lifetime victimization and perpetration were low (1–2 times). Perpetrators most often targeted their friends and alcohol was typically a factor in victimization. Over half of victims reported experiencing positive social outcomes as a result of being victimized and about a third reported negative emotional outcomes. Findings suggest that experiences of body vandalism are relatively common, especially in young adults, associated with alcohol consumption, and result in both positive and negative outcomes for victims. This study offers evidence for BV as an outcome of social drinking, suggests contexts that increase the risk of BV occurrence, and provides a foundation from which future studies can build. Highlights: Common types of body vandalism were the addition of writing, objects, or substances. Most victims of body vandalism are also perpetrators. Body vandalism is associated with alcohol use for both perpetrators and victims. Body vandalism victimization results in both positive and negative consequences.